ANALISIS SALURAN TATANIAGA DAN MARJIN TATANIAGA KELAPA DALAM DI KABUPATEN TANJUNG JABUNG TIMUR - Wulandari, Siti Abir; Rogayah (Agripita Publisher, 2017)
Jambi provinces produce oil with a total production of 105 255 tonnes and the average productivity of 0.9 tonnes / ha of the total area of 120 254 ha. East Tanjung Jabung amounting to 50 254 tons with an average productivity of 0.85 tons / ha. The low price of grain at the farm level coconuts become the main obstacle in the field of business administration. Farmers do not have the power to determine the price to the consumer. The purpose of this study was to determine the channel margin trading system and trading system in the coconut palm in East Tanjung Jabung, Jambi Province. This research was conducted in East Tanjung Jabung, Jambi Province In this study, sampling is done with Snowball sampling method. The population is in a coconut trader. This research was conducted by survey method and descriptive analysis (qualitative and quantitative) and to see the margin trading system used since the early registration price (manufacturer) to the end (consumer) marketing system. An analysis of the share farmer's helpful to knowpart of the price received by farmers from the price of consumer level expressed as a percentage. Results from the study shows that there are two (2) channels coconut trading system that provides different grades margin trading system. I channel margin Rp. 700, - / Btr and channel margin II Rp. 960.5 / Btr. The portion of the price received by farmers from the price the consumer level is at 69.37%.